2021
DOI: 10.3390/microorganisms9061220
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of Clustered Regularly Interspaced Short Palindromic Repeats (CRISPRs) in Pandemic and Non-Pandemic Vibrio parahaemolyticus Isolates from Seafood Sources

Abstract: Vibrio parahaemolyticus is one of the significant seafood-borne pathogens causing gastroenteritis in humans. Clustered regularly interspaced short palindromic repeats (CRISPR) are commonly detected in the genomes of V. parahaemolyticus and the polymorphism of CRISPR patterns has been applied as a genetic marker for tracking its evolution. In this work, a total of 15 pandemic and 36 non-pandemic V. parahaemolyticus isolates obtained from seafood between 2000 and 2012 were characterized based on hemolytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In this study, the antibiotic resistance patterns among V. parahaemolyticus indicated that 12 (30%) of isolates had significant MAR index values above 0.2, while the highest MAR index value above 0.3 indices occurred among two strains of O1:K25 and O10:KUT serovars isolated from DMF and MOI sites, respectively. This agrees with other studies elsewhere that detected an MAR index above 0.2 among 45% of pandemic and non-pandemic V. parahaemolyticus isolated from seafood [69]. The MAR indices that exceed 0.2 indicated that these isolates originated from high-risk contamination and may pose human risks [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the antibiotic resistance patterns among V. parahaemolyticus indicated that 12 (30%) of isolates had significant MAR index values above 0.2, while the highest MAR index value above 0.3 indices occurred among two strains of O1:K25 and O10:KUT serovars isolated from DMF and MOI sites, respectively. This agrees with other studies elsewhere that detected an MAR index above 0.2 among 45% of pandemic and non-pandemic V. parahaemolyticus isolated from seafood [69]. The MAR indices that exceed 0.2 indicated that these isolates originated from high-risk contamination and may pose human risks [70,71].…”
Section: Discussionsupporting
confidence: 92%
“…Although self-limiting, strains of V. parahaemolyticus are virulent enough to cause outbreaks and can be fatal ( Jung, 2018 ). With recent reports of antimicrobial-resistant strains ( Tan et al, 2020 ; Jingjit et al, 2021 ), there is an urgent need to tackle it.…”
Section: Discussionmentioning
confidence: 99%
“…The host range of phage OPA17 was tested against V. campbellii ( n = 118) isolates obtained in this study and from a previous report ( 27 ). Other species of vibrios used in host range determination include V. alginolyticus ( n = 4), V. parahaemolyticus ( n = 7) ( 57 59 ), V. vulnificus ( n = 5) ( 60 ), and one each of V. furnissii and V. harveyi ( Table 1 ). The spot assay was performed to assess the lytic spectrum of the phage based on the bacterial susceptibility pattern.…”
Section: Methodsmentioning
confidence: 99%